Do Group Sectors Explain the Determinants of Cash Holding for U.S. Public Firms? - Zhou, Shaobo (2012)
This paper investigates whether group sectors explain the determinants of corporate cash holding behaviour for a sample of U.S. public firms. We focus on investigating the determinants of corporate cash holding based on different sector groups by using OLS model and fixed effect model. We find that these sector groups behave dramatically differently in the respect of holding cash. In addition to this, we perform a yearly evolution analysis for our full sample and then for our sector groups separately. To provide comparable results, we use both leverage ratio and net leverage measure and find that net leverage measure capture the inverse relationship between debt and cash holdings better than leverage ratio for our sample. During our sample period, we also observe that all of our sector groups exhibit a positive trend in cash ratio, indicating that U.S. public firms seem to hold more cash over the sample period. More important, we find that most of our sectors tend to hold more cash in the period of global financial crisis. However, the Technology sector is an exception that seems to have fewer incentives to build up cash during crisis period.